Efficacy of using Zaontz urethral stent in hypospadias repair by the Face, Legs, Activity, Cry, Consolability (FLACC) scale: A prospective study - Ozcan, Serkan; Bagcioglu, Murat; Karakan, Tolga; Diri, Mehmet Akif; Demirbas, Arif (Canadian Urological Association Journal, 2017)
Introduction: The developments in hypospadias surgical techniques and materials are intended to improve surgery outcomes and patient comfort. The aim of this study is to determine the effect of the Zaontz urethral stent (ZUS) (Cook Medical) on patient comfort and surgical success rates in children undergoing hypospadias surgery. Methods: A feeding tube was used to repair 46 cases of primary distal hypospadias, and ZUS (6F, 8F, and 10F in diameter) was used to repair to 31 cases of primary distal hypospadias between December 2009 and June 2011 in our clinic. ZUS was compared with the feeding tube in terms of surgical success rates and patient comfort in assessments made during postoperative periods. Results: The patients with ZUS were followed with a stent for seven days postoperatively, as were the patients with the feeding tube. There was no statistical difference between the two groups in terms of fistula formation (p>0.05). Patient comfort was evaluated by the Face, Legs, Activity, Cry, Consolability (FLACC) scale on the first and third postoperative days, and a statistically significant difference was observed in favour of ZUS on the third postoperative day (p<0.05). Conclusions: Compared with a feeding tube in hypospadias repair, ZUS does not make any contribution to the urinary fistula rates. However, ZUS may have an advantage in terms of patient comfort in the postoperative followup. On the other hand, the small number of patients and the high price of the ZUS were the most important limitations. Prospective, randomized trials are needed to assess efficacy and cost.